Mapeamento da qualidade nutricional da alimentação em diferentes estados do Brasil - André Bento Chaves Santana; Flavia Mori Sarti (Confins)
The investigation of food consumption characteristics in diverse population groups presents substantial importance in the public health scenario, considering the need for insight on the effects of the nutritional transition in the occurrence and distribution of global burden of chronic non-communicable diseases link to dietary factors. Indicators for evaluation of dietary quality have been proposed for global assessment of food consumption patterns registered based on the main nutritional characteristics of the diet. The Revised Healthy Eating Index (IQD-R) is an instrument adapted and validated for application in Brazil, allowing the evaluation of the dietary quality for individuals and population groups in the country. Thus, the present study proposed to analyze the nutritional quality of the diet of the population in different Brazilian states using the IQD-R, based on data of food consumption patterns registered in a nationwide representative survey, according to level of per capita income. The results obtained point to IQD-R score of 56.85 for the Brazilian population. Considering geographic distribution, there was lower quality of diet in Amapa (54.31), Sergipe (55.13) and Rio Grande do Sul (55,24); whilst there was better dietary quality score in the states of Mato Grosso (59. 74), Alagoas (59.74) and Maranhao (60.31). Additionally, higher nutritional scores were identified among individuals in lower income levels, in comparison to the rest of the Brazilian population. The consumption of calories from processed and ultraprocessed foods comprising 50% or higher proportion of the total dietary intake was associated with lower IQD-R scores, being identified differences in the index scores according to location of residence. These evidences show wide range of variation in the nutritional quality of the Brazilian food consumption pattern, particularly related to differences in relation to socioeconomic and cultural characteristics of the population living in diverse Brazilian states.